2016
DOI: 10.1161/circoutcomes.115.002127
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differential Effects of Obesity on Health-Related Quality of Life via Obesity-Related Comorbidities

Abstract: T he prevalence of obesity has increased dramatically over the last decades in many industrialized countries, such that they are experiencing what has often been referred to as an obesity epidemic.1 Average body mass index (BMI) worldwide has increased by ≈0.5 kg/m 2 per decade since the 1980s, and an estimated 500 million adults were considered obese (BMI ≥30 kg/m 2 ) in 2008. 2 The trends in France are consistent with this general pattern, with an average relative increase in BMI of almost 6% per year since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 46 publications
5
34
0
1
Order By: Relevance
“…The modification effect by gender was found in the US population of patients, with greater negative effects of overweight and obesity on quality of life among women than men (Katz et al 2000). Similar results were obtained in France but with proportionally lower effects mediated by obesity-related conditions (Audureau et al 2016).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The modification effect by gender was found in the US population of patients, with greater negative effects of overweight and obesity on quality of life among women than men (Katz et al 2000). Similar results were obtained in France but with proportionally lower effects mediated by obesity-related conditions (Audureau et al 2016).…”
Section: Discussionsupporting
confidence: 66%
“…Among men, an indirect effect through obesity-related conditions was observed. This research concluded that women suffer a burden of excess weight due to an interplay of different factors within a psychosocial process, rather than medical conditions (Audureau et al 2016). There are studies indicating the association between obesity and depression or other psychological disorders and that they are modified by gender.…”
Section: Discussionmentioning
confidence: 93%
“…The excess weight derived from an obesity situation is a major risk factor to suffer other NCDs. Based on literature research, some of the comorbidities associated with overweight and obesity are cardiometabolic factors, including risk factors (hypertension, hyperlipidemia, and Type II Diabetes Mellitus), cardiovascular diseases, asthma, and musculoskeletal disorders [ 23 , 24 , 25 ]. When a patient is classified as Obese with a BMI greater than or equal to 30 kg/m , the risk of comorbidities is considered as severe [ 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…1. According to Baron and Kenny (38), evidence for a partial mediating effect was assessed by the statistical significance (38)(39)(40)(41)…”
Section: Outcomementioning
confidence: 99%